HOW THE FREQUENCY OF PAIN IN THE EARLY STAGES OF PARKINSON’S DISEASE AFFECTS THE SPEED OF DIAGNOSIS - Bedia Samancı; Nazlı Durmaz Çelik; Başar Bilgiç; Serhat Özkan; Haşmet Ayhan Hanağası (İstanbul Tıp Fakültesi Dergisi)
Objective: The fact that non-motor symptoms such as pain in Parkinson’s disease (PD) are more associated with musculoskeletal diseases (MSD) suggests that there may be delays in diagnosis. The aim of this study was to review the first symptoms of PD, especially pain, while at the same time reviewing the medical specialists to whom patients first went and examining the effects of these parameters on time to diagnosis and treatment. Materials and Methods: Patients with PD were included. The patients were evaluated in terms of clinical features, initial complaints and onset time, presence and type of pain, the medical specialist they first applied to, and time to diagnosis. Results: Eighty-six patients were included (42 female, 44 male). The first complaints were bradykinesia, tremor, tremor and bradykinesia, shoulder pain, tremor and painful cramps. These complaints started 10.1±5.22 years previously, and the diagnosis of PD was made 8.56±4.87 years previously on average. The first specialist departments to which patients with these complaints applied were Neurology (n=34), Physical Therapy and Rehabilitation (n=34), Neurosurgery (n=10), and Orthopedics (n=8). The first admission to Neurology was 8.7±4.85 years previously. Pain complaints started 7.2±6.69 years before the first admission in 56 patients. Musculoskeletal pain was 86%, dystonic pain was 25%, central pain and neuropathic pain were 11% each in the group of patients who had experienced pain. Conclusion: PD can be confused with MSD due to findings such as pain and rigidity, which may cause a delay in diagnosis and treatment. This delay can be prevented if non-neurologyspecialists are provided with more detailed training about the disease, and if public awareness is raised about the signs and symptoms of PD.